Research on installation solution of eddy current braking devices on EMU bogies - LIU Chao; ZHAO Wenxue; FAN Jun; HAN Qingli; CHEN Bingzhi (机车电传动, 2025)
This research explored a solution for installing linear eddy current braking devices on the bogies of existing 400 km/h EMUs, aiming to make their braking systems more economical and environmentally friendly. Adaptive improvements were made to the bogie frame and axle box structures, taking into account the bogie structure and clearance requirements. To ensure the safety and reliability of the modified structures, static strength and fatigue strength simulations were conducted on the bogie frame components and the axle box assembly, followed by verification through bench tests. The service life of the axle box bearings was calculated based on the proportions of eddy current braking conditions: released, applied, and faulty. Additionally, the dynamic performance of the entire vehicles was simulated under the eddy current brake releasing and application conditions. The results indicate that the modified bogie components are structurally safe and reliable, thus meeting the requirements for safe operation at high speeds. The proposed solution provides a reference for the design of eddy current braking systems for high-speed EMUs.